The Roles of Drug Metabolism-Related ADH1B in Immune Regulation and Therapeutic Response of Ovarian Cancer - Xu, Zhijie; Peng, Bi; Kang, Fanhua; Zhang, Wenqin; Xiao, Muzhang; Li, Jianbo; Hong, Qianhui; Cai, Yuan; Liu, Wei; Yan, Yuanliang; Peng, Jinwu (Frontiers in Cell and Developmental Biology, 2022)
The different pharmacological effects of drugs in different people can be explained by the polymorphisms of drug metabolism-related genes. Emerging studies have realized the importance of drug metabolism-related genes in the treatment and prognosis of cancers, including ovarian cancer (OV). In this study, using comprehensive bioinformatics and western blot, we identified that the drug metabolism-related gene, ADH1B, was significantly down-regulated in OV cells and tissues. The patients with high level of ADH1B presented a good prognosis. We also found negative correlation between ADH1B expression and the activity of chemotherapeutic agents, such as cyclophosphamide. In addition, the positive correlations were observed between ADH1B expression and multiple immune checkpoints, including LAG3 and HAVCR2 . The immune infiltration analysis further indicated that aberrantly expressed ADH1B might have important roles in regulating the infiltration of macrophages and neutrophils in OV tissues. Then, the co-expression analysis was conducted and the top three enriched KEGG pathways were spliceosome, RNA transport and DNA replication. In conclusion, drug metabolism-related gene ADH1B and its interactive network play an essential role in the immune regulation and therapeutic response, and may be identified as promising therapeutic targets for OV patients.